THE POLISH FITNESS SERVICES MARKET IN TURBULENCE CONDITIONS - BUHAIENKO, Tetiana; LIANNOI, Mykhailo; TONKOPEI, Yuliia; GVOZDETSKA, Svitlana; SIECHYN, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article presents the results of the analysis of the state of the modern Polish market of fitness services in turbulent conditions. A thorough comparison of the Polish fitness services market with the corresponding European market was made and the prospects for its development were outlined. Attention is focused on the fact that throughout the world the issue of maintaining a personal level of health and a physically developed body has always been and remains relevant. It has been confirmed that in various historical eras, available means were used for this, the main ones of which were and remain physical culture and sports. Today, the adult population of the developed countries of the world is offered a wide range of sports, physical culture and health, recreational, sports, and mass services, and their free choice. Зростання попиту на такі послуги сприяє популяризації та швидкому розвитку фітнес-індустрії в країнах Європи. Незважаючи на наявність на ринку кожної європейської країни великих відомих брендів фітнес-центрів, основний дохід в цій галузі припадає саме на заклади малого та середнього бізнесу. Польща за щорічним доходом в цій галузі не є лідером на європейському ринку здоров’я та фітнесу і посідає сьоме місце в загальноєвропейському рейтингу. Проте політика держави у сприянні охорони здоров’я, запропоновані програми покращення благополуччя працівників, поява нових фітнес-технологій та урбанізація очікувано мають вплинути на зростання доходу в цій сфері вже до кінця 2026 року. The slowdown in the development of the fitness industry in Poland, as well as in other European countries, was significantly influenced by the period of lockdown and social distancing caused by the Covid-19 pandemic. A significant advantage in promoting the services of fitness centers in Poland with domestic capital (compared to similar fitness centers with foreign investments) is MultiSport cards. This means that the owners of such cards have the right to use the services of sports and recreational facilities throughout the country. It is safe to say that the fitness industry in Poland is well-developed and makes a greater contribution to the country’s economy than most other sectors of leisure services.